The S-layer Protein DR_2577 Binds Deinoxanthin and under Desiccation Conditions Protects against UV-Radiation in Deinococcus radiodurans - Farci, Domenica; Slavov, Chavdar; Tramontano, Enzo; Piano, Dario (Frontiers in Microbiology, 2016)
Deinococcus radiodurans has the puzzling ability to withstand over a broad range of extreme conditions including high doses of ultraviolet radiation and deep desiccation. This bacterium is surrounded by a surface layer (S-layer) built of a regular repetition of several proteins, assembled to form a paracrystalline structure. Here we report that the deletion of a main constituent of this S-layer, the gene DR_2577, causes a decrease in the UVC resistance, especially in dessicated cells. Moreover, we show that the DR_2577 protein binds the carotenoid deinoxanthin, a strong protective antioxidant specific of this bacterium. A further spectroscopical characterization of the deinoxanthin-DR_2577 complex revealed features which could suggest a protective role of DR_2577. We propose that, especially under dessication, the S-layer shields the bacterium from incident ultraviolet light and could behave as a first lane of defence against UV radiation.